INTERGRATED ENVIRONMENTAL LAW SYSTEM STRATEGIES TO ADAPT CLIMATE CHANGE IMPACT FROM ENERGY RESILIENCE IN INDONESIA - Maret Priyanta (Jurnal Dinamika Hukum, 2017)
Climate change issues are solicitous and affect every nation due to its impact on human living and other living things. International cooperation through the international convention on climate change such as United Nations Framework Convention on Climate Change needed as an effort for finding the solution for the problem especially the legal aspect. Energy as resources is identified as one of the sources directly contributing to global warming. As a part of the environment, energy resilience needs to support Indonesia commitment to the global society. This paper describes the academic perspective in environmental law by applying principle and norm approach to analyze the climate change issues in Indonesia related to energy resilience. The recommendation analyzes the issue based on legal research with a descriptive analytical methodology to describe the comprehensive idea about the problem and solution in climate change issues and environmental law in Indonesia law system perspective.Keywords: Climate, Energy, Environmental, Law, Resilience.